DETERMINANTS OF SMEs PROFITABILITY: DO FIRM SIZE AND AGE STILL MATTERS? - Ibrahim, Muhamad Wahid; Niagasi, Ariq Fikria; Trisyandhi, Yusuf Farrel (This journal is published by the Vocational School of Universitas Sebelas Maret., 2024)
Small and medium-sized firms (SMEs) are critical to the global economy because they create jobs and contribute to economic growth (ILO, 2019). This study examines the profitability of SMEs using the return on asset ratio, as well as the effect of size and age on profitability, by examining data samples from 106 enterprises in Indonesia's industry sector over a ten years. In total, 1060 pieces of data were examined in this study. The goal of this study is to comprehend the current state of SMEs' profitability and to identify the effect of age and size, as many scholars have various opinions on the subject. To evaluate the effect of size and age on the observed SMEs, multiple linear regression analysis was used. According to the findings, the average SME profitability in Indonesia, as assessed by the return on assets ratio, was only 1.1%, which is relatively low. Size also has a beneficial effect on profitability, as shown by the data. Furthermore, contrary to the hypothesized premise, age has a detrimental impact on the profitability of SMEs. Finally, this study identifies potential limits and suggests strategic implications for policymakers, SME management, and future research.